2022
DOI: 10.3389/fnut.2021.779306
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal Polyunsaturated Fatty Acids With Telomere Length in the Cord Blood and Placenta in Chinese Population

Abstract: Few studies have investigated the correlation between maternal polyunsaturated fatty acids (PUFAs) and telomeres in offspring, and the underlying influential mechanisms. In this study, we assessed the associations of maternal PUFAs with telomere length (TL) and DNA methylation of the telomerase reverse transcriptase (TERT) promoter in the cord blood and the placenta. A total of 274 pregnant women and their newborn babies were enrolled in this study. Maternal blood before delivery, the cord blood, and the place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Shortened TL among fetuses exposed to maternal high fat consumption during pregnancy, after accounting for the effects of potential covariates, was recorded in the Salihu et al study [96]. However, according to the Liu et al study, concentrations of total n3-PUFAs and docosahexaenoic acid (DHA) in maternal erythrocytes, are closely correlated to infant TL and the telomerase reverse transcriptase (TERT) promoter methylation [94]. Contradictory evidence for maternal PUFA status and its relation to offspring TL was recorded in the cohort study by Yeates et al [95].…”
Section: Maternal Nutrition and Placental And Newborn Telomeresmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortened TL among fetuses exposed to maternal high fat consumption during pregnancy, after accounting for the effects of potential covariates, was recorded in the Salihu et al study [96]. However, according to the Liu et al study, concentrations of total n3-PUFAs and docosahexaenoic acid (DHA) in maternal erythrocytes, are closely correlated to infant TL and the telomerase reverse transcriptase (TERT) promoter methylation [94]. Contradictory evidence for maternal PUFA status and its relation to offspring TL was recorded in the cohort study by Yeates et al [95].…”
Section: Maternal Nutrition and Placental And Newborn Telomeresmentioning
confidence: 99%
“…In terms of dietary lipids, one study examined the effect of n3 intake on umbilical cord, placenta, and infant TL. Maintaining higher levels of maternal n3 polyunsaturated fatty acids (PUFAs) during pregnancy may help maintain TL in the offspring, which is beneficial to long-term offspring health [94].…”
mentioning
confidence: 99%
“…It has also been recently reported the effect of maternal intake of n-3 PUFAs during pregnancy influences the offspring DNA methylation [ 197 ]. Also, it has been recently shown that maternal n-3 PUFAs supplementations are closely correlated to infant telomere length [ 198 ]. However, the long-term effect of maternal intake of n-3 PUFAs in reducing future risk of metabolic and cardiovascular diseases in the offspring is unknown.…”
Section: Micronutrientsmentioning
confidence: 99%
“…In terms of dietary lipids, one study examined the effect of omega-3 intake and their effect on umbilical cord, placenta and infant TL. Keeping higher levels of maternal n-3 polyunsaturated fatty acids (PUFAs) during pregnancy, may help maintain TL in the offspring, which is beneficial to longterm offspring health [94].…”
Section: Maternal Nutrition Placental and Newborn Telomeresmentioning
confidence: 99%
“…Shortened TL among fetuses exposed to maternal high fat consumption during pregnancy, after accounting for the effects of potential covariates, was recorded in the Salihu, et al [96], but with no association recorded for a high carbohydrate diet. However, according to Liu et al study concentrations of total n3-PUFAs and docosahexaenoic acid (DHA) in maternal erythrocytes, are closely correlated to infant TL and the telomerase reverse transcriptase (TERT) promoter methylation [94]. Maternal n-3 PUFAs (a-linolenic, eicosapentaenoic and docosahexaenoic acids) in cord blood and the placenta correlated to infant TL and TERT promoter methylation, differently in cord blood and the placenta.…”
Section: Maternal Nutrition Placental and Newborn Telomeresmentioning
confidence: 99%